THE EFFECT OF SERVICE QUALITY, PERCEPTION OF QUALITY AND BRAND IMAGE ON PURCHASE DECISIONS : (Case Study at the Consumer Center By Yu Tum Gunungkidul) - azwar azwar; Rinda Ardina Dewi; Chicita Murdiningrum (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2022)
This study aims to analyze the effect of Service Quality, Perceived Quality, and Brand Image on Consumer Purchase Decisions of Yu Tum Gunung Kidul Souvenir Center. The object of this research is the Yu Tum Souvenir Center with a sample of 100 respondents. This type of research is descriptive and quantitative, with a purposive sampling technique. The data were processed using SPSS 25. The results showed that: (1) Service Quality partially had a significant positive effect on the Yu Tum Souvenir Center's consumer purchasing decisions, and (2) Quality perceptions partially had a significant positive effect on the Souvenir Center's consumer purchasing decisions. By Yu Tum, (3) Brand Image partially has a significant positive effect on Consumer Purchase Decisions of Yu Tum Souvenir Center (4) Service Quality, Perceived Quality, Brand Image simultaneously have a significant positive effect on Consumer Purchasing Decisions of Yu Tum Souvenir Center.